Reviewing The Integration of Islamic Studies and Science in Islamic Religious Universities in Indonesia - Ubaidila, Syafik; Khoirul Mustamir, Ahmad (Journal of World Science, 2023)
This article examines the Policy of Integrating Islamic Science and Science in Islamic Universities. Policy of Integration of Science and Islamic Studies in Islamic Higher Education. In general, this policy is like the government's response to science development, which was born from the conflict between science and religion. This study uses a literature review approach by citing and reviewing reading sources according to the research focus. The results of this study indicate that the Policy of Integrating Islamic Sciences and Sciences in Islamic Universities has not shown the government's concern for the development of science. The integration policy through the Ministry of Religion of the Republic of Indonesia following Minister of Religion Regulation Number 10 of 2010 concerning Organization and Work Procedures does not want to control the pace of scientific development. However, PTKAI's spirit of campus integration is not solely due to the policies of the Indonesian Ministry of Religion following Minister of Religion Regulation Number 10 of 2010 concerning Organization and Work Procedures, but rather the enthusiasm to continue scientific development. The policy of integrating Islamic knowledge and science in Islamic Religious Higher Education has not shown the government's concern for knowledge development.